PHSYCOANALYSIS LACAN IN HEROINE CHARACTERIZATION ON “BLOODY CHAMBER” BY ANGELA CARTER - Rida Rahmawati; Wahyu Mala Indah Rohmana (BASA Journal of Language & Literature, 2023)
The Novella title "The Bloody Chamber" is a fairy tale story that is a fairy tale novel that takes a feminist point of view. This study aims to explore the characterization of the Heroine in the story through psychoanalysis Lacan. the method used in this analysis is the library research method with feminist criticism. The researcher found that the three-phase pass by Heroine in the story 1. the real phase when Heroine first feels married and feels an undescribed feeling. 2. Imaginary phase, when Heroine begins to identify her surroundings and discover her identity. and 3. the symbolic phase, when Heroine discovers the reality of the Marquise and the Bloody Chamber